Karakter Suara Limnonectes modestus (Boulenger, 1882) Asal Suaka Margasatwa Nantu, Gorontalo, Sulawesi Bagian Utara - Kurniati, Hellen; Hamidy, Amir (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTCall characteristics of Limnonectes modestus (Boulenger, 1882) which is endemic to Sulawesi have never been described before.  The advertisement calls of two individual males collected from Nantu Wildlife Sanctuary, Gorontalo, northern Sulawesi were recorded in December 6, 2014 at air temperatures of 26°C.  Adobe Audition 3.0 software was used to visualize sound waves.  Advertisement call of L. modestus is very simple, which only has one type of call containing 1-6 pulses.  Pulse duration, pulse rate and call rate of the two individual males are very diverse, ranged between 21-56 milli seconds, 2.58 to 7.87 pulses/second and 0.09-1.16 call/second; but the frequency variation of call is very low, the lower frequency range between 515.6 to 593.0 Hertz (CV=3.1%), whereas the upper frequency range between 2179.0 to 2859.0 Hertz (CV=5.4%); the band width of the frequency range between 1616.5 to 2320.0 Hertz (CV=7.1%). Key words: vocalization, Limnonectes modestus, Nantu Wildlife Sanctuary, North Sulawesi